Manajemen Kepala Sekolah Dalam Meningkatkan Mutu Lulusan di SMK Ma’arif 9 Kebumen - Umi Salamah; Eliyanto Eliyanto; Maryanto Maryanto (Tarbi: Jurnal Ilmiah Mahasiswa, 2023)
The purpose of this study was to find out how the management applied by the principal in improving the quality of graduates at SMK Ma'arif 9 Kebumen and how the obstacles faced and solutions were taken in an effort to improve the quality of graduates at SMK Ma'arif 9 Kebumen. The research approach uses a qualitative approach. The data obtained using the method of observation, interviews and documentation. While the data analysis technique used qualitative data analysis. The conclusions of this study are: 1) The management applied by the principal in improving the quality of graduates at SMK Ma'arif 9 Kebumen uses several steps, namely: a) Plan, which is the stage where problem identification is carried out and designs appropriate steps to be taken, in order to find a solution to a problem. Planning for the quality of graduates at SMK Ma'arif 9 Kebumen is carried out at the beginning of each learning year at the time of making the curriculum and making work programs for learning activities. b) Do, which is the stage where the plans that have been made are implemented. The implementation of the management of improving the quality of graduates at SMK Ma'arif 9 Kebumen is carried out under the supervision of the principal and deputy principal. c) Check/Control, namely so that the implementation of the graduate quality improvement program can run well and achieve the expected target. The principal of Ma'arif 9 Kebumen Vocational School in implementing the quality improvement program for graduates of the school principal conducts periodic control by involving the waka of the curriculum, waka of student affairs, homeroom teachers, and BK teachers. d) Act, namely conducting a total evaluation of the results of targets and processes and following up with improvements. SMK Ma'arif 9 Kebumen made improvements after analyzing the results of the tryout and looking at the competencies that had not been fully absorbed by doing remedial and material enrichment.